Fachspezifische und fachübergreifende Argumentation am Beispiel von Schöpfung und Evolution Theoretische Grundlagen - Empirische Analysen - Jugendtheologische Konsequenzen - Weiß, Thomas (2016)
The study is in the German-speaking area the first and only one, which empirically evaluates the argumentation skills of students (n=48) at the high school level. It furthermore draws consequences for the research in youth theology. As the technical didactical background served creation as a narration about a good beginning, and evolution as a description of the origin and development of different species. This made it possible to explore the communication form "arguing" in this fundamental research of the pedagogy of religion not only subject-specific but across different subjects. The results show that the researched students argue and thereby use different patterns subject-specific but also across different subjects. However, it remains unclear, whether they use these patterns consciously.